Developmental anatomy and apical organization of the primary root of cork oak (Quercus auber L. (International Journal of Plant Sciences, 1999)
Using histological techniques, we investigated the development and organization of the primary root and the root apex of Quercus suber L. (cork oak), a Mediterranean woody species growing in semiarid conditions. The presence of a quiescent center was also investigated. The histogenesis of the vascular system begins with the maturation of the protophloem elements. Primary phloem and xylem strands form alternately, and maturation proceeds centripetally, although xylem differentiation does not reach the center of the root, which is occupied by a pith. Most protoxylem elements were fully mature well before the endodermis entered State I with the formation of the Casparian strip. A continuous vascular cambium forms before the initiation of the phellogen in the outermost pericyclic layer. In the primary root the apex has an open organization with four groups of initials: vascular cylinder initials, cortical initials, lateral root-cap initials, and columella initials. The quiescent center includes the vascular initials and some derivatives. These features contrast with the radicle in mature and germinating embryos that have a closed organization with three groups of initials and a wider quiescent center.